INTESTINAL OBSTRUCTION IN CHILDREN AT EL OBEID HOSPITAL, WESTERN SUDAN. - Doumi, El Bushra Ahmed; Mohamed, Mohamed Ibrahim; Abbakar, Awadalla Musa; Bakhiet, Mohamed Yousof; Bashier, Mohamed Babelrahma (Gezira Journal of Health Sciences, 2010)
Background: Intestinal obstruction is a common cause of childhood surgical emergency in the developing countries with considerable morbidity and mortality. Objectives: To assess the magnitude, pattern and management outcomes of intestinal obstruction in children presenting to a General Surgical Unit at a rural setup, in Western Sudan. Patients and Methods: The clinical records of all children below 15 years of age admitted to the University General Surgical Unit at El Obeid Teaching Hospital, in Western Sudan with the diagnosis of intestinal obstruction during the period from 2006 to 2007 were retrospectively reviewed. The mean age, gender, causes of obstruction and management outcomes were studied and analyzed. Results: There were 72 patients.  48 were males (66.7%). Neonates and infants were 70% of patients. Hirschsprung’s disease, intussusception, obstructed hernias and ano-rectal anomalies accounted for 21.8%, 19.4%, 16.7% and 13.9% respectively. Less common causes were pyloric stenosis 8.3% and gut atresia 6.9%. Lymphoma, adhesions, peritonitis and faecal impaction were 2% each. The overall mortality rate was 13.9%. Conclusions: The main causes of childhood intestinal obstruction at Western Sudan were congenital anomalies in neonates, intussusception in infants and obstructed hernias in elder children. The management was associated with high mortality due to poor hospital facilities and late presentations resulting in bowel ischaemia.